Elasticidade-juros da demanda de investimentos: uma análise histórico comparativa - Mello, Cristina Helena Pinto de (1993)
The purpose of the presente máster dissertation is to analyse the impacto of changes in the interest rate on the level of investment; seeking to answer if it is powerful as an instrument of macroeconomic policy to estimulate the autor believes that interest rate affect investment but it is a bad instrument to recuperate the level of investment. To achieve this answer the master dissertation is organized as follow; in the first part a survey with the main theories and recent developments about the investment decision is showed; in the second part the author construct a panel showing the differences between the years and in the last part, two questionaires, applied in different decades, are compared to show the impact of different cenarios.